Relationship between clay minerals and microorganisms in underground hydrogen storage reservoirs: a mini review - Allison Clark; Shikha Sharma (Frontiers in Energy Research)
Hydrogen (H2) will play a vital role in the global shift towards sustainable energy systems. Due to the high cost and challenges associated with storing hydrogen in large quantities for industrial applications, Underground Hydrogen Storage (UHS) in geological formations has emerged as a promising solution. Clay minerals, abundant in subsurface environments, play a critical role in UHS by providing low permeability, cation exchange capacity, and stability, essential for preventing hydrogen leakage. However, microorganisms in the subsurface, particularly hydrogenotrophic species, interact with clay minerals in ways that can affect the integrity of these storage systems. Microbes form biofilms on clay surfaces, which can cause pore clogging and reduce the permeability of the reservoir, potentially stabilizing H2 storage and limiting injectivity. Microbial-induced chemical weathering, through the production of organic acids and redox reactions, can degrade clay minerals, releasing metal ions and destabilizing the storage site. These interactions raise concerns about the long-term storage capacity of UHS, as microbial processes could lead to H2 loss and caprock degradation, compromising the storage system’s effectiveness. This mini review aims to cover the current understanding of the interactions between clay minerals and microorganisms and how these dynamics can affect the safe and sustainable deployment of UHS.